2021
DOI: 10.1177/15589447211017221
|View full text |Cite
|
Sign up to set email alerts
|

Dorsoradial Capsulodesis for Stage I Trapeziometacarpal Joint Arthrosis

Abstract: Background: Thumb trapeziometacarpal (TM) joint arthrosis is a common cause of thumb pain, which adversely affects hand function. Early arthrosis is characterized by capsular laxity, painful pinch and grip, and physical findings of joint tenderness and laxity. Dorsoradial capsulodesis (DRC) is a surgical technique used to stabilize the TM joint and treat early-stage arthrosis. We aim to evaluate the clinical outcomes of DRC for treating trapeziometacarpal instability in early-stage disease. Methods: Between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Eight studies incorporated the VAS scores as part of their outcome measurements, and five studies reported the pre- and postoperative VAS scores ( Table 3 ). 7 , 34 , 37 , 36 , 40 , 42 , 43 The tendon-looping procedure using the PL tendon and TCL flap reported the most notable improvement in mean VAS scores, which improved from 6 (range 5–7) preoperatively to 0.5 (range 0–1) postoperatively. 40 Dorsal stabilization using an internal brace, 34 volar thermal capsulorrhaphy, 37 and the Eaton and Littler technique by Spekreijse et al.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Eight studies incorporated the VAS scores as part of their outcome measurements, and five studies reported the pre- and postoperative VAS scores ( Table 3 ). 7 , 34 , 37 , 36 , 40 , 42 , 43 The tendon-looping procedure using the PL tendon and TCL flap reported the most notable improvement in mean VAS scores, which improved from 6 (range 5–7) preoperatively to 0.5 (range 0–1) postoperatively. 40 Dorsal stabilization using an internal brace, 34 volar thermal capsulorrhaphy, 37 and the Eaton and Littler technique by Spekreijse et al.…”
Section: Resultsmentioning
confidence: 96%
“… 34 , 35 Eleven publications consisting of 12 studies that met the inclusion and exclusion criteria were analyzed for qualitative review, including one randomized controlled trial (RCT), 36 six before-after studies, 34 , 36 , 37 , 38 , 39 , 40 and five observational studies. 7 , 35 , 41 , 42 , 43 These articles reported a total of 216 patients, 230 thumbs, and 9 different surgical techniques ( Tables 1 and 2 ). The included studies reported the surgical outcomes with long-term follow-up ranging from 12 months to 15 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperatively, patients were immobilized in a thumb spica splint which was removed alongside the K-wire at 4 week follow-up. In a subsequent cases series, Koehler and Rayan 16 evaluated outcomes of these patients treated with dorsoradial ligament capsulodesis and K-wire fixation. They reported a median VAS pain score at 6 months of 0.5 with 77% of patients reporting no pain.…”
Section: Discussionmentioning
confidence: 99%